Efficacy and safety of anterior transposition of the ulnar nerve for distal humerus fractures: A systematic review and meta-analysis - Li, Ting; Yan, Jingxin; Ren, Qiuyu; Hu, Jiang; Wang, Fei; Xiao, Chengwei; Liu, Xilin (Frontiers in Surgery, 2023)
Background This systematic review and meta-analysis was performed to summarize available evidence of anterior transposition of the ulnar nerve for patients with distal humerus fractures. Materials and Methods The databases were searched from PubMed, Cochrane, Embase, Scopus, Web of Science, Chinese National Knowledge Infrastructure (CNKI), Chongqing VIP Database (VIP), and Wan Fang Database up to June 2022. The clinical outcome included operation time, fracture healing time, hospital stays, elbow joint function, and ulnar neuritis rate. Statistical analysis was performed with Review Manager 5.3 (Cochrane Collaboration). Results A total of 17 studies were included (8 RCTs and 9 retrospective studies), and 1280 patients were analyzed. The results of this meta-analysis showed anterior transposition group had longer operation time (MD = 20.35 min, 95%CI: 12.56–28.14, P < 0.00001). There was no significant difference in fracture healing time (SMD = −0.50, 95%CI: −1.50–0.50, P = 0.33), hospital stays (MD = −1.23 days, 95%CI: −2.72–−0.27, P = 0.11), blood loss (MD = 2.66 ml, 95%CI: −2.45–7.76, P = 0.31), and ulnar neuritis rate (OR = 1.23, 95%CI: 0.63–2.42, P = 0.54) between two groups. Finally, elbow joint motion, elbow joint function, fracture nonunion, and post-operative infection (P > 0.05) between two groups were not significantly statistic difference. Conclusion This meta-analysis showed that anterior transposition group is not superior to non-transposition group for patients with distal humerus fractures without ulnar nerve injury. On the contrary, non-transposition group have shorter operation time than that of anterior transposition group. Non-transposition group did not increase the post-operative ulnar neuritis rate. Therefore, both anterior transposition group and non- transposition group are the treatment options for patients with distal humerus fractures without ulnar nerve injury. Besides, these findings need to be further verified by multi-center, double-blind, and large sample RCTs.